2010
DOI: 10.3844/erjsp.2010.104.110
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of the Optimum Heat Pipe Heat Exchanger for a Condenser of Vapor-Compression Refrigeration Cycle

Abstract: Problem statement: This study theoretically investigated applying heat pipe as a heat exchanger in the condenser of vapor compression refrigeration system for sustainable well-being. Splittype air conditioner for residential propose was considered. To reduce pressure drop and recover heat from the condensing process of the refrigeration cycle, this investigation tried to use Closed Loop Oscillating Heat Pipe (CLOHP) instead of the conventional condenser in split-type air conditioner. Approach: The system was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Only few researchers have considered PHP in the place of a condenser to improve the COP of a refrigeration system. Pracha Yeunyongkul et.al [8] experimentally investigated the application of a closed loop PHP as a condenser for a vapour compression refrigeration system using R-22 as a refrigerant. The results showed that the efficiency rating of closed loop PHP was higher than conventional condenser by 13.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Only few researchers have considered PHP in the place of a condenser to improve the COP of a refrigeration system. Pracha Yeunyongkul et.al [8] experimentally investigated the application of a closed loop PHP as a condenser for a vapour compression refrigeration system using R-22 as a refrigerant. The results showed that the efficiency rating of closed loop PHP was higher than conventional condenser by 13.4%.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lot of research studying the effect of the total cost on the optimum size and shape in terms of engineering. (Jinghua et al, 2009;Ozel and Pihtili, 2007;Bolatturk, 2006;Soylemez and Unsal, 1999;Soponpongpipat et al, 2010;Yeunyongkul et al, 2010) Conveyor design has been studied for a long time and there has been development on its design technique. For example, Tsalidi and Dentsoras (1997) illustrated the design of conveyor by applying design parameters space search technique.…”
Section: Introductionmentioning
confidence: 99%